2019
DOI: 10.1177/1933719118783266
|View full text |Cite
|
Sign up to set email alerts
|

High Level of APOA1 in Blood and Maternal Fetal Interface Is Associated With Early Miscarriage

Abstract: Early miscarriage (EM) is one of the most devastating obstetrical complications globally affecting the quality of women's life. In the present study, we aimed to identify proteins that correlate with and could act as biomarkers for EM. We performed 2-dimensional gel electrophoresis in chorionic villi samples followed by mass spectrometry for identification of differential protein expression with EM. Proteomic studies detected a total 124 protein spots, out of which 83 spots were differentially expressed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…APOA1 is related to embryo quality, development, and survival. Studies have indicated that APOA1 expression is significantly increased in chorionic villi, decidua, and serum of patients with IVF and early abortion, and Verma' results also proved that APOA1 expression in the villi of IVF patients was increased [ 53 ] . Furthermore, APOE plays a major role in antiphospholipid functional attenuation (APL), inducing pregnancy complications [54] .…”
Section: Discussionmentioning
confidence: 87%
“…APOA1 is related to embryo quality, development, and survival. Studies have indicated that APOA1 expression is significantly increased in chorionic villi, decidua, and serum of patients with IVF and early abortion, and Verma' results also proved that APOA1 expression in the villi of IVF patients was increased [ 53 ] . Furthermore, APOE plays a major role in antiphospholipid functional attenuation (APL), inducing pregnancy complications [54] .…”
Section: Discussionmentioning
confidence: 87%
“…APOA1 is related to embryo quality, development, and survival. Studies have indicated that APOA1 expression is signi cantly increased in chorionic villi, decidua, and serum of patients with IVF and early abortion, and Verma' results also proved that APOA1 expression in the villi of IVF patients was increased [53] . Furthermore, APOE plays a major role in antiphospholipid functional attenuation (APL), inducing pregnancy complications [54] .…”
Section: Discussionmentioning
confidence: 87%
“…Another study reported altered serum lipids profiles among women with a threatened miscarriage, including diminished concentrations of LDL cholesterol, total cholesterol, and phospoholipids 24 . There are also a few previous studies which found that greater Apolipoprotein A-I might is associated with an increased likelihood of miscarriage 25,26 .…”
Section: Discussionmentioning
confidence: 95%
“…It is clear that the metabolism of phospholipids changes during pregnancy 30,31 , but we do not fully understand if and what impact this may have on ensuring a healthy pregnancy. With regard to some of the other specific metabolites measured, Apolipoprotein A-I is an immunomodulator, and is shown to inhibit myeloid derived suppressor cell recruitment, which is known to regulate maternal pregnancy tolerance ensuring an intact pregnancy 25,26 .…”
Section: Discussionmentioning
confidence: 99%